Environmental Management and Analysis of the Rational and Ecologically Correct Use of Natural Resources and their Processes in the Technology Center of the Federal University of Ceará - Oliveira, Ivan de; Gadelha, Francisco Ernane Abreu (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This research deals with environmental management and the treaties related to the topic.  Addresses the environmental planning and the rational use of natural resources. Performs a case study in the technology Center of UFC (CT), about the pattern of consumption of water, electrical energy, paper and the destination of waste generated in the process. The methodological approach of this work uses the following types of research: literature, field and exploratory. In the field research was applied to a questionnaire; supplement it with interviews of main managers. The exploratory research was also used in defining goals and finding more information about the subject. The results have supplied the hypotheses, and showed that CT has social and environmental characteristics, however, has not an environmental management program structured and makes wastes.  The search also indicated that CT should participate in the Environmental Agenda for Public Administration (A3P), tool to promote systematic improvement of its processes.